Cholescintillography: Preliminary report based on 50 cases - di Genio, Susana; Bogliaccini, Gustavo; Lago, Graciela; Gaudiano, Javier; Lorenzo, Mirta; Mut, Fernando; Touya, Eduardo; Touya, Eduardo; Praderi, Raúl (Cirugía del Uruguay, 1981)
Report en a new non invasive procedure far morphologic and functional exploration of the biliary tract.